how would I check this on my own? I know you put numbers in the place of the letters but when I do that I come up with my moms answer. this is what i have when I check my work. p=-2 q=3

6*(-2)*3 =-36 but 3(-2)(-2*3)=36 could you tell me what i'm doing wrong when I check them pls simplify expression
3(-p)(-2q) = 6pq

2 answers

3(-p)(-2q) = 6pq is correct like Ms Sue confirmed for you

to check: you let p=-2 and q=3

3(-p)(-2q) = 3(2)(-6) = -36
6pq = 6(2)(-3) = -36

since left side = right side, you had the right answer.
ok I see what I was doing wrong I was doing wrong thank you and my mom thanks you